Classification of Low Back Pain according to Treatment Based Classification Algorithm: A Cross-Sectional Study at Tertiary Center of Nepal - Pokharel, Mukesh; Acharya, Ranjeeta S (Annapurna Journal of Health Sciences, 2023)
Background: Low Back Pain (LBP) is the commonest musculoskeletal disorder in Nepal. Treatment Based Classification (TBC) categorizes individual with LBP in four different categories. They are manipulation, stabilization, specific and traction subgroup and are evident to have better outcome. The aim of our study is to classify LBP patient according to TBC and evaluate whether LBP patient fall in one particular subgroup or a combination of subgroup. Methods: A cross-sectional study was conducted in Dhulikhel hospital, Physiotherapy department using convenience sampling. The study was conducted in 65 (Female/35) patients with acute and sub-acute LBP. Patient information on LBP duration, pain diagram, Numerical Pain Rating Scale, and Fear Avoidance Belief Questionnaire were obtained. After standardized assessment, patients were categorized according to TBC. Results: Approximately half of LBP patients fell into one subgroup i.e., 47.7%, 27.7% into combination of two or three subgroups and 20% did not meet any criteria for TBC. Similarly, patients falling in specific, stabilization, manipulation and traction sub-groups were 44.61%, 43.07%, 16.92% and 12.30% respectively. Our study concluded that almost half of the patients categorized into one subgroup. Categorization according to TBC is feasible and can be performed to provide an optimal treatment for patients visiting Dhulikhel Hospital.